Predicting playing status in professional water polo players: Analysis by gender - Vila, M. H.; Manchado, C.; Abraldes, J. A.; Ferragut, C. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: The aim of this study was twofold: firstly, to identify the characteristics of water polo players that discriminate between women and men based on specific playing positions; and secondly to develop a predicting model to identify the characteristics that are best suited to a given playing position based on gender. METHODS: The study included 130 professional water polo players. Anthropometric characteristics and throwing velocity were analyzed in different situations: no defender or goalkeeper, goalkeeper only and the players made three rapid arm movements and then threw the ball at maximum speed without further feinting with goalkeeper. Measured variables were compared according to gender and player position using discriminant analysis. RESULTS: The predictive model accurately classifies 71.1% of the male players using three variables (arm span, muscle mass Lee and penalty without goalkeeper), and 64.7% of the female players using three variables (triceps skinfold, biceps skinfold and anteroposterior chest breadth). CONCLUSIONS: The anthropometric characteristics and throwing velocity play an important role in identifying the different specific positions in male and female water polo players. In female players, the variables that were determinant in the predictive model, were those associated with body composition.